Enhancing the climate resilience of America's natural resources - Vance, Wendy Hayden (Climate change and its causes, effects, and prediction series., 2015)
President Obama has made it clear that we have a moral obligation to our children and future generations to leave behind a planet that is not polluted and damaged. That is why, as part of his effort to combat climate change, the President launched a Climate Action Plan last year to cut carbon pollution, prepare communities for the impacts of climate change, and lead international efforts to address this global challenge. This book discusses building community resilience by strengthening America's natural resources and supporting green infrastructure; and examines President Obama's Climate Acti.